A Comparison of Molecular Typing Methods Applied to Enterobacter cloacae complex: hsp60 Sequencing, Rep-PCR, and MLST - Roberto Viau; Lee M. Kiedrowski; Barry N. Kreiswirth; Mark Adams; Federico Perez; Dror Marchaim; Dubert M. Guerrero; Keith S. Kaye; Latania K. Logan; Maria Virginia Villegas; Robert A. Bonomo (Case Western Reserve University, 2017)
Molecular typing using repetitive sequenced-based PCR (rep-PCR) and hsp60 sequencing were applied to a collection of diverse Enterobacter cloacae complex isolates. To determine the most practical method for reference laboratories, we analyzed 71 E. cloacae complex isolates from sporadic and outbreak occurrences originating from 4 geographic areas. While rep-PCR was more discriminating, hsp60 sequencing provided a broader and a more objective geographical tracking method similar to multilocus sequence typing (MLST). In addition, we suggest that MLST may have higher discriminative power compared to hsp60 sequencing, although rep-PCR remains the most discriminative method for local outbreak investigations. In addition, rep-PCR can be an effective and inexpensive method for local outbreak investigation.